Early Withering of Enlarged Ovules in Pollinated Fruits of Bananas (Musa spp.) Suggest Abortion after Fertilization - Waniale, Allan; Mukasa, Settumba B.; Tugume, Arthur K.; Kubiriba, Jerome; Tushemereirwe, Wilberforce K.; Tumuhimbise, Robooni (Horticulturae, 2022)
Sterility in edible bananas is as a result of a long history of anthropogenic-driven selection for sterile genotypes, since seed is not desirable in fruit pulp for human consumption. However, this poses a challenge to conventional genetic improvement by slowing breeding pipelines. In this study, we investigated whether pollen tubes reach all parts of the ovary, the position of fertilized ovule development in fruits, and potential seed set in selected banana genotypes. We selected four cultivars of East African Highland Cooking bananas (EAHBs), a Matooke hybrid ‘222K-1’, improved diploid ‘2905’, and wild bananas ‘Zebrina (G.F.)’ and ‘Calcutta 4’. There was evidence of pollen tubes in the distal, mid and proximal sections of the fruit, irrespective of hand position and genotype. Fertilization, as indicated by an increase in ovule size, happened along the entire length of the fruit but complete development was biased at the distal end in some genotypes. There were some differences in ovule fertilization rates between hands, with distal hands having more ovules and higher ovule fertilization rates. Ovule fertilization happens in bananas but the vast majority aborts, especially at the proximal end of the ovary. Ovule fertilization rates are generally much lower than available ovules.
Keywords: Banana pollination; Pollen tubes; Ovule fertilization; Ovule abortion